To find which expressions will result in a total of 0 when added to \(-5 - 7 + 3\), we first need to simplify \(-5 - 7 + 3\):
\[ -5 - 7 = -12 \] \[ -12 + 3 = -9 \]
Now we have \(-9\) and we want to find expressions that, when added to \(-9\), will equal 0. This means we need to find expressions that equal \(9\) because:
\[ -9 + x = 0 \quad \Rightarrow \quad x = 9 \]
Now let's evaluate each expression:
-
\(2 - (-7)\): \[ 2 - (-7) = 2 + 7 = 9 \]
-
\(-2 - 7\): \[ -2 - 7 = -9 \]
-
\(7 - (-2)\): \[ 7 - (-2) = 7 + 2 = 9 \]
-
\(-7 - (-2)\): \[ -7 - (-2) = -7 + 2 = -5 \]
Now we summarize the results:
- \(2 - (-7) = 9\) (this works)
- \(-2 - 7 = -9\) (does not work)
- \(7 - (-2) = 9\) (this works)
- \(-7 - (-2) = -5\) (does not work)
Thus, the expressions that would result in a total of 0 when added to \(-5 - 7 + 3\) are:
1. \(2 - (-7)\)
3. \(7 - (-2)\)